The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/jre.12544
|View full text |Cite
|
Sign up to set email alerts
|

The potential of salivary biomarkers for predicting the sensitivity and monitoring the response to nonsurgical periodontal therapy: A preliminary assessment

Abstract: Salivary IL-1β and MMP-8 might be useful for diagnosing periodontitis and monitoring the recovery of periodontitis following nonsurgical periodontal therapy. MMP-8 and lactoferrin showed potential for predicting the sensitivity to the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 58 publications
1
17
0
1
Order By: Relevance
“…Furthermore, higher NGAL levels in local samples, that is, gingival crevicular fluid (GCF), were reported in patients with periodontitis (Pradeep, Nagpal, Karvekar, & Patnaik, ). The present salivary NGAL data are therefore intriguing and warrant further study, but it is remarkable that conflicting data also exist for other salivary inflammatory markers in periodontitis, for example, with increased (Lee et al, ) or similar (Moura et al, ) salivary levels of IL‐1β compared to healthy controls. While the main contributor to salivary proteins is the circulation, with proteins shed from local oral surfaces playing a lesser role (Lynge Pedersen & Belstrom, ), disease‐specific mechanisms are likely to be involved, for example, with periodontitis‐dependent increased expression of inflammatory mediators in the inflamed oral tissue potentially being countered by increased local tissue binding or other interactions that contribute to unpredictability of salivary levels of these molecules.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, higher NGAL levels in local samples, that is, gingival crevicular fluid (GCF), were reported in patients with periodontitis (Pradeep, Nagpal, Karvekar, & Patnaik, ). The present salivary NGAL data are therefore intriguing and warrant further study, but it is remarkable that conflicting data also exist for other salivary inflammatory markers in periodontitis, for example, with increased (Lee et al, ) or similar (Moura et al, ) salivary levels of IL‐1β compared to healthy controls. While the main contributor to salivary proteins is the circulation, with proteins shed from local oral surfaces playing a lesser role (Lynge Pedersen & Belstrom, ), disease‐specific mechanisms are likely to be involved, for example, with periodontitis‐dependent increased expression of inflammatory mediators in the inflamed oral tissue potentially being countered by increased local tissue binding or other interactions that contribute to unpredictability of salivary levels of these molecules.…”
Section: Discussionmentioning
confidence: 72%
“…Saliva is the fluid of the oral cavity, which besides being critical to maintenance of oral homeostasis harbors various biological substances such as the salivary microbiota and inflammatory markers (Lynge Pedersen & Belstrom, ). The presence of untreated periodontitis has been shown to alter the composition of the salivary microbiota (Belstrom et al, ) and increase salivary levels of inflammatory proteins such interleukin (IL)‐1β and matrix metalloproteinase (MMP)‐8 (Lee, Chen, Tu, Wu, & Chang, ; Liukkonen, Gürsoy, Pussinen, Suominen, & Könönen, ; Sorsa et al, ). Thus, the composition of the salivary microbiota and salivary levels of inflammatory markers have been suggested as a proxy of oral and systemic health status (Yoshizawa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The potential of salivary IL-1β and MMP-8 to predict the response to treatment has been reported in a few studies. Lee et al (2018) found that the baseline levels of IL-1β and MMP-8 in saliva…”
Section: F I G U R Ementioning
confidence: 99%
“…Using saliva as a diagnostic fluid for point-of-care analysis for periodontal diseases is advantageous because sample collection is easy and non-invasive, and there is access to plentiful biological fluid (Korte & Kinney, 2016). Some biomarkers in saliva have been shown to be related to the treatment response to SRP (Lee et al, 2018;Nagarajan et al, 2019;Sexton et al, 2011) and could potentially be used to estimate the treatment response to SRP.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been suggested that IL1β can discriminate between inactive and active periodontal lesions, there are very few diagnostic accuracy studies that have investigated it in saliva as a way to evaluate the response to periodontal treatment (Lee, Chen, Tu, Wu, & Chang, 2018; Shyu et al, 2015). The methodological approach in the present paper is different because we evaluate for the first time the capacity of IL1β in saliva to distinguish untreated from treated periodontitis demonstrating clinical improvement and differentiating between non‐smokers and smokers.…”
Section: Discussionmentioning
confidence: 99%